Evaluation of the safety in dogs of long‐term, daily oral administration of capromorelin, a novel drug for stimulation of appetite. Issue 3 (25th September 2016) - Zollers, B.; Huebner, M.; Armintrout, G.; Rausch‐Derra, L. C.; Rhodes, L.
Abstract : The objective of the study was to evaluate the safety of capromorelin, a ghrelin agonist that stimulates appetite and causes increased body weight and the release of growth hormone (GH). Beagle dogs ( n = 32) received either oral placebo or 0.3, 7, or 40 mg/kg capromorelin once daily for 12 consecutive months. Safety was evaluated by physical examinations, including ECG and ophthalmic examinations, and comprehensive clinical pathology. Serum levels of capromorelin, GH, and insulin‐like growth factor 1 (IGF‐1) were measured periodically. Necropsies and histopathological evaluations were performed at study termination. As expected, GH and IGF‐1 levels were mildly increased in capromorelin‐treated dogs. Adverse events were limited to mild emesis and loose stools in all groups and excess salivation among some dogs receiving higher capromorelin doses. Clinical pathology testing was generally normal, although blood lipids and alkaline phosphatase levels were moderately increased among dogs receiving capromorelin. Treated dogs had slightly longer post‐treatment PR intervals seen on ECG, but with no changes in cardiac histopathology. Postmortem findings were normal. Drug‐related increases in liver weight were linked to overall increases in body weight. Capromorelin was well tolerated in dogs at daily doses up to 40 mg/kg for 12 months, demonstrating a wide safety margin.